Pendidikan Nilai Budaya dan Folklore Di lingkungan Keluarga Etnis Bungku dalam Perspektif Sejarah - Windayanti; Andriansyah (Jurpis: Jurnal Pendidikan Ilmu Sosial, 2021)
Until now, the Bungku Community has instilled character or cultural values ​​in the next generation. Thus, this paper is expected to provide a method, model and media that can be used as reference material in the process of educating children about cultural values ​​and character in the Bungku ethnic family environment in accordance with the cultural values ​​they profess. This paper will use historical methodology in collecting data related to the problems to be studied. The successful data and information are then classified. Furthermore, it is analyzed whether the data and information are related to the topic discussed or not, the next step is interpretation by finding and determining meaning. Thus, it can be assembled into a unified whole in written form.